The new Everyman dictionary of music - Cummings, David 1942-; Blom, Eric 1888-1959 (Everyman's reference library., 1988)
Over 10,000 entries cover composers, performers, instruments, orchestras, influences, styles, technical terms, listings of over 2,000 musical works, and premier performances.